(untitled) (Research, Society and Development, 2021)
Objectives: To assess the knowledge of caregivers and their oral health practices in hospitalized children with cancer, in addition to reporting the main oral complications resulting from cancer treatment. Methodology: Cross-sectional study with 34 caregivers of children with cancer hospitalized at the Oncology Control Foundation of the State of Amazonas (FCECON), aged 0-12 years. Results: Of the caregivers, 70.6% were female, predominantly mothers (70.6%), aged between 31 and 40 years (52.9%), single (52.9%) and unemployed (73, 5%). Only 32.8% received oral hygiene instructions, with the dentist being the source of these in only 32.4% of cases. Most caregivers performed their children’s oral hygiene three times a day (76.5%), using only a toothbrush and toothpaste (61.8%). Only 23.5% of children reported discomfort in the oral cavity and 97.1% of caregivers reported that the inclusion of the Dental Surgeon in the health team was important. Among the oral manifestations after cancer treatment, the most prevalent were changes in taste (32.4%) and dry mouth (26.5%). The hospital stay was up to 7 days (61.8%) and the treatment time was over one year (34.4%). Conclusion: There was a lack of information from caregivers about oral hygiene practices and the difficulty in understanding the importance of oral health for the maintenance of systemic health, despite reporting the frequent occurrence of dysgeusia and oral dryness, which can negatively influence the success of medical treatment and even lead the patient to death.